Long-term survival and secondary procedures after open or endovascular repair of abdominal aortic aneurysms - van Schaik, Theodorus G; Yeung, Kak K; Verhagen, Hence J; de Bruin, Jorg L; van Sambeek, Marc R H M; Balm, Ron; Zeebregts, Clark J; van Herwaarden, Joost A; Blankensteijn, Jan D (Journal of vascular surgery, 2017)
Randomized trials have shown an initial survival benefit of endovascular over conventional open abdominal aortic aneurysm repair but no long-term difference up to 6 years after repair. Longer follow-up may be required to demonstrate the cumulative negative impact on survival of higher reintervention rates associated with endovascular repair. We updated the results of the Dutch Randomized Endovascular Aneurysm Management (DREAM) trial, a multicenter, randomized controlled trial comparing open with endovascular aneurysm repair, up to 15 years of follow-up. Survival and reinterventions were analyzed on an intention-to-treat basis. Causes of death and secondary interventions were compared by use of an events per person-year analysis. There were 178 patients randomized to open and 173 to endovascular repair. Twelve years after randomization, the cumulative overall survival rates were 42.2% for open and 38.5% for endovascular repair, for a difference of 3.7 percentage points (95% confidence interval, -6.7 to 14.1; P = .48). The cumulative rates of freedom from reintervention were 78.9% for open repair and 62.2% for endovascular repair, for a difference of 16.7 percentage points (95% confidence interval, 5.8-27.6; P = .01). No differences were observed in causes of death. Cardiovascular and malignant disease account for the majority of deaths after prolonged follow-up. During 12 years of follow-up, there was no survival difference between patients who underwent open or endovascular abdominal aortic aneurysm repair, despite a continuously increasing number of reinterventions in the endovascular repair group. Endograft durability and the need for continued endograft surveillance remain key issues.